Analisis Dampak Pemberian Reward Dan Punishment Bagi Motivasi Belajar Siswa Di SD - Mai Sri Lena; Sahrun Nisa; Rizka Khairani; Silvi Wardahtun Aisyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of this study was to determine the impact of reward and punishment for students at SD Negeri 08 Sarilamak. In this study, researchers used a qualitative descriptive approach. The method used is the method of observation and interviews. The research location was carried out at SD Negeri 08 Sarilamak. The results of the study show that student learning motivation is related to the teacher giving rewards and punishments to students on the condition that they are given properly and appropriately. Giving rewards is related to how the teacher teaches students about good values in which students are given awards if they do good or positive things. Conversely, the teacher will give punishment if students do something that is not good or negative. This is so that students do not repeat the negative actions or violations that they have committed.